The impact of governance in developing the performance of Al-Rafidain Bank, an exploratory study for the period 2018-2021 - Al-Eidani, Zaid (The Gulf Economist, 2022)
The research is based on the importance of the role of governance in developing the performance of Rafidain Bank. Since there is no agreement on the concept of governance, but there is an agreement on its application to enhance performance development in institutions and support their ability to face any financial crisis they may be exposed to. The research depended on the analytical descriptive approach, and a questionnaire was designed and distributed to 144 employees and included four dimensions (two of the independent variable (the guiding principles of governance of Rafidain Bank) and the dependent variable (performance development in the Rafidain Bank). Statistical methods were used to analyze the data and discuss the results. To a set of results, the most important of which is that Rafidain Bank has various plans to improve the level of services provided to customers (clients). The field of technology makes it difficult to facilitate the procedures of the auditors, in addition to the existence of a statistically significant impact relationship between the independent variable (justice, disclosure and transparency) on the approved variable to develop the performance of the Rafidain Bank (efficiency, effectiveness).